PENERAPAN MODEL PAIKEM DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI DI KELAS X SMAN 6 PONTIANAK - Ade Mardiana, Indah Putri; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is "the application of the PAIKEM model in improving student learning outcomes in sociology subject in class X SMAN 6 Pontianak". This study aims to determine the implementation of the application of the PAIKEM model and determine the magnitude of the influence of the PAIKEM model in improving student learning outcomes in sociology learning in class X of SMAN 6 Pontianak. The form of the experiment used in this study was a quasi-experimental. The population in this study was class X SMAN 6 Pontianak academic year 2018/2019. The sample used was class X IPS 4 (experimental class) and class X IPS 1 (control class). The data collection tool used in this study is the learning outcomes test in the form of essay questions (pretest and posttest) and questionnaire sheets in the form of the application of the PAIKEM learning model. Analysis of learning outcomes data using the Mann Whitney U-test with a real level = 5% obtained Sig.0,000. This shows that there are significant differences in learning outcomes and student responses. The calculation of the effect size (ES) is obtained at 0.92 which belongs to the large category, which gives an effect of 51.6%. Student responses to the application of the PAIKEM model belong to the category of "very good" which is equal to 89.02%.Â Keywords: Application, PAIKEM Model, Learning OutcomesÂ